Aesthetic Crown Lengthening for Gummy Smile Treatment Related to Altered Passive Eruption: A Case Report: Estetis Crown Lengthening untuk Perawatan Gummy Smile yang Berhubungan dengan Altered Passive Eruption: Sebuah Laporan Kasus - Apriantika, Indira; Krismariono, Agung (TALENTA, 2020)
A healthy and beautiful smile can affect appearance and confidence. One of the aesthetic problems in dentistry that is often complained of by patients is excessive gingival display (gummy smile). The excessive gingival display can be caused by several factors, one of which is altered passive eruption (APE). One of the treatments to correct gummy smile related to APE is crown lengthening. Crown lengthening can be with bone reduction (gingivectomy with bone reduction) or without bone reduction (gingivectomy). Crown Lengthening with bone reduction is a surgical procedure that aims to maintain the dentogingival complex and to improve smile aesthetics. The purpose of this case report is to determine the crown lengthening with bone reduction (gingivectomy with bone reduction) procedure as a gummy smile treatment related to APE .A23-year-old female patient, came to Dental Hospital of Universitas Airlangga with complaints of her upper gum which not in the same length and the teeth looked short, she considered her smile was less aesthetic. After conducting analyses relating to aesthetics and periodontal tissue, crown lengthening with bone reduction was chosen for this patient treatment. The treatment results are quite good, visible gingival margins that matched the gingival zenith and improved patient's smile profile. APE as the etiology of patient's gummy smile can be corrected. There are no post-surgical complications such as excessive pain and infection. A proper diagnosis, treatment plan, and good techniques can produce a harmonious smile on the patient.